Threshold model for hot events spreading based on relative impact weight of the user - De-yang ZHANG; Yi-liang HAN; Xiao-long LI; Feng PAN; Yi-xing ZHOU (网络与信息安全学报)
A new relative influence weight function was proposed in combination with the existing linear threshold model.Combining with the information itself sensitivity and the threshold characteristic of the node itself,a threshold model(URLT model) was proposed,which can measure the information communication ability.By simulating the spread of different networks,different sensitivity information and different node thresholds,and comparing the final propagation situation,the experimental results show that the final influence range is consistent with the real spread situation.Therefore,the model has some reference value for the discovery and suppression of the law of information dissemination.